Pengembangan Buku Pengayaan Menulis Teks Berita Terintegrasi Nilai Kebhinekaan Global sebagai Sumber Belajar Kontekstual untuk Penguatan Krakter Peserta Didik SMP/MTs - Wiliyana, Markhamah; Sulistyaningrum, Septina (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – Students learning outcomes in writing news texts remain low, partly due to the limited availability of learning resources in schools. They also have not yet been able to apply global diversity values effectively. Therefore, it is necessary to develop an enrichment book as supplementary material in the learning process. This study aims to develop a News Writing Enrichment Book with Global Diversity Values and to assess its feasibility through expert validation.Method – This research employed a Research and Development (R&D) method based on Sugiyono’s model, which consists of five stages: needs analysis, data collection, product design, design validation, and revision. The study involved teachers and students from three junior high schools, with data collected through observation, interviews, and questionnaires.Findings – The research findings indicate that both teachers and students require an enrichment book as a companion resource to meet learning needs effectively. The results of the expert validation show that the developed enrichment book achieved an average feasibility score of 95.3%, categorized as highly feasible for use in the learning process. Research Implications – The enrichment book contributes to improving students’ skills in writing news texts while simultaneously integrating global diversity values that strengthen student character in accordance with the Pancasila Student Profile. Furthermore, it encourages students to understand, respect, and appreciate the cultural diversity present in their surroundings.